La mise en récit de l'expérience d'un évènement traumatique se pense-t-elle dans les mêmes termes qu'un récit « ordinaire » ? - Marie Hèlène Verneris (Université de Provence, 2020)
This article is part of the biographical research whose story is the heart of his theoretical reflection. The author hypothesizes that the experience of the story from extreme situations cannot be experienced or even thought of in the same terms as an "ordinary" story. After having defined certain multidisciplinary theoretical benchmarks in the fields of psychoanalysis, psychology and psychiatry, she offers to explore the perspective of biographical research on the notion of traumatic event. The author is based on the example of two life stories, each evoking a very different disaster scenario, from which will follow many dramatic situations over which the narrators will have no control. The author shows that while the experiences of traumatic events are not all equivalent, not all are equally apprehended by the story. The comparative analysis of their narrative will shed light on several major common characteristics. With the need to tell, and to be recognized, the two narrators associate the need to transmit a story that must be shared collectively in order to regain, in dignity, the right to be a man, and that to be a woman. Although diificult to deliver, the narrative of their story is inscribed in their lives as an act of survival.